Pengaruh Leverage, Growth Opportunity, Ukuran Perusahaan dan Intensitas Modal terhadap Konservatisme Akuntansi (Studi Empiris pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016-2019) - Edison Edison; Ratih Rosita; Asrini Asrini; Esti Susilawati (Universitas Batanghari Jambi, 2023)
This study aims to examine the effects of leverage, growth opportunity, firm size and capital intensity on the accounting conservatism simultaneously and partially. The population in this research is the bank company listed on the Indonesia Stock Exchange (IDX). Sample selection technique used is purposive sampling and obtained 28 companies with research period year 2016-2019. Data analysis method used in this research is multiple linear regression analysis using software SPSS version 22 for Windows. The results show that leverage, growth opportunity, firm size and capital intensity simultaneously affect the accounting conservatism and firm size have an effect on to accounting conservatism partially. While partially, leverage, growth opportunity, capital intensity have no effect on the accounting conservatism.